ANÁLISE CROMOSSÔMICA COMPARATIVA ENTRE POPULAÇÕES DE Apareiodon affinis (Actinopterygii: Characiformes: Parodontidae) - Coelho, Karina de Almeida (2014)
Basic and molecular cytogenetic studies were carried out in Apareiodon affinis (Parodontidae) of five populations: Passa Cinco River, Ipeúna – SP; Piracicaba River, Piracicaba – SP; Paraná River (lake of the Itaipu dam - Santa Helena – PR) all belong to Upper Paraná River hidrografic system and; two localities of the Paraguay River drainage, Cuiabá River, Cuiabá - MT and, Paraguay River, Cáceres - MT. The conventional analysis showed that the three populations of the Upper Paraná River system have 2n = 54 chromosomes to males and 2n= 55 chromosomes to females. Those differences in the chromosome number are due to by presence of sex chromosome system showing female heterogamety ZZ/ZW1W2 type. The karyotypic formula and fundamental number (FN) for these three populations was 50 m/sm + 4 st. FN = 108 to males and; 49 m/sm + 6 st, FN = 110 to females. The sex chromosomes Z was characterized as the largest metacentric, while the chromosome W1 and W2 appears to be subtelocentrics and have half the size of the Z chromosome. In turn, the population of the Cuiabá River, Cuiabá – MT have 2n = 54 chromosome to males and females, karyotypic formula 42 m/sm + 2 st + 10 a and FN = 98 and; the Paraguay River population show 2n = 54 chromosomes and no heteromorphic sex chromosomes system and, karyotypic formula 36 m/sm + 2st + 16 a. Fluorescence in situ hybridizations (FISH) com 18S and 5S ribosomal DNAs were performed in the different populations of A. affinis, resulting in (i) a single metacentric chromosome pair bearing 5S rDNA sites for the samples on the Upper Paraná River, (ii) a heteromorphic situation of a chromosome metacentric and one acrocentric for the population of the Cuiabá River and; (iii) a acrocentric pair bearing 5S rDNA sites for the population of the Paraguay River. The 18S rDNA was found in the terminal region of the long arm of a subtelocentric pair in all populations. This situation is considered a sinapomorfic feature in Parodontidae when compared with the sister group Anostomidae. FISH with pPh2004 satellite DNA was also performed in all the populations of this study showing positive hybridization in differential sites: 3-4 pairs all m/sm in the Upper Paraná River samples and; 6-8 st/a pairs in the Paraguay River samples. Thus, the cytogenetic differences observed between Upper Paraná and Paraguay Rivers populations is possible to affirm the occurrence of a high karyotipic differentiation in gene flow restriction. Lower cytogenetic differentiation can be observed also when compared samples from the same river system. Thus, is possible to state that A. affinis of the Upper Paraná River population is divergent and should have their taxonomic condition reviewed.